Avaliação da silagem de milho das variedades granífera e forrageira no desempenho de bovinos das raças nelore e cachim em regime de confinamento - Spadotto, Anselmo José; Silveira, Antonio Carlos [UNESP]; Furlan, Luiz Roberto; Arrigoni, Mario de Beni [UNESP]; Costa, Ciniro [UNESP]; De Oliveira, Henrique Nunes; Parré, Claudinei (My University, 1996)
The experiment was carried out to evaluate corn grain and corn forage varieties productivity and nutritive value for silage comparing to the performance of Nellore and Canchim cattle in a feedlot. A completely randomized design was used with a 2 x 2 factorial arrangement based on two breeds (Nellore and Canchim) and two corn varieties (grain and forage). Harvest was made after 120 days sowing, when plants showed more than 2/3 of dry. leaves and grains were in dough stage. The silage was stored in a 400 tons. The experimental diet consisted of grain and forage corn silage, 7,2 liters of liquid yeast (1,5 kg of dry yeast/ head/day) and 1,1 kg of ground corn (1,0 kg of dry matter/head/day). The experiment duration was 110 days, with a 20 days adaptation period and 90 days for data collection. Animals were regularly weighted every 28 days. It was concluded that corn grain was more appropriate for silage than corn forage, and in the same stage it showed a higher dry matter content and a 41.3% higher grain yield, promoting higher weight gain and better feed/gain ratio in the feedlot beef cattle.
Grain corn silage and forage corn silage evaluation on the of Nellore and Canchim cattle performance in feedlot
Keywords: Canchim; Corn silage; Nellore; Performance